2018
DOI: 10.1021/acsomega.7b01982
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fully Organic Water Oxidation Electrocatalysts: A Quest for Simplicity

Abstract: Despite the growing need for readily available and inexpensive catalysts for the half-reactions involved in water splitting, water oxidation and reduction electrocatalysts are still traditionally based on noble metals. One long-standing challenge has been the development of an oxygen evolution reaction catalyzed by easily available, structurally simple, and purely organic compounds. Herein, we first generalize the performance of the known N-ethyl-flavinium ion to a number of derivatives. Furthermore, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…12 More recently, Bachmann and co-workers observed OER catalysis by pyridinium ions (MePy + , MePyz + , and MePym + , Scheme 1) and found that the catalytic efficiency directly correlates with the electrophilic character of the iminium ion (the best behavior was observed with MePy + ). 13 Considering that the electrophilic nature of iminium cations appears to play a crucial role in cocatalysis, we extended our investigation to an electron-deficient xanthylium cation Xan 2+ (Scheme 1). Generally, xanthylium cations exhibit low pseudobase pK a , 15 which reflects their Lewis acidity.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…12 More recently, Bachmann and co-workers observed OER catalysis by pyridinium ions (MePy + , MePyz + , and MePym + , Scheme 1) and found that the catalytic efficiency directly correlates with the electrophilic character of the iminium ion (the best behavior was observed with MePy + ). 13 Considering that the electrophilic nature of iminium cations appears to play a crucial role in cocatalysis, we extended our investigation to an electron-deficient xanthylium cation Xan 2+ (Scheme 1). Generally, xanthylium cations exhibit low pseudobase pK a , 15 which reflects their Lewis acidity.…”
mentioning
confidence: 99%
“…While the oxidation potential of Xan 2+ is significantly higher than the thermodynamic potential for OER, the potential can be lowered using iminium-based cations, such as flavinium or pyridinium systems studied previously. 11,13 The list of oxides that strongly bind *O species is available through computational 24,25 and experimental 29 studies. In synergy with Lewis acid cocatalysts presented in Scheme 2, these oxides are expected to show accelerated OER activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The redox and photochemical versatility of flavins has been extensively exploited for their use outside of a biological environment as molecular catalysts in organic synthesis, , targeted drug delivery, , sensing applications, ,, optoelectronics, ,, and as catalysts for water oxidation. Moreover, synthetic flavins have gained an elevated interest as functionalization of the flavin isoalloxazine backbone provides insight to, and possible improvement of, the flavin redox and photochemical properties. The C6-C9 positions on the benzene moiety and the N3 and N10 positions on the isoalloxazine unit have been the primary areas for functionalization and have been shown to alter the photophysical properties of flavins (see Scheme for numbering).…”
Section: Introductionmentioning
confidence: 99%